Group decision making approach based on interval-valued intuitionistic linguistic geometric aggregation operators. (1st January 2013) - Wang, Xin-Fan; Wang, Jian-Qiang; Yang, Wu-E
In this paper, a new concept of interval-valued intuitionistic linguistic number (IVILN), which is characterised by a linguistic term, an interval-valued membership degree and an interval-valued non-membership degree, is first introduced. Then, score function, accuracy function and some multiplicative operational laws of IVILNs are defined. Based on these two functions, a simple approach for the comparison between two IVILNs is presented. Based on these operational laws, some new geometric aggregation operators, such as the interval-valued intuitionistic linguistic weighted geometric (IVILWG) operator, interval-valued intuitionistic linguistic ordered weighted geometric (IVILOWG) operator and interval-valued intuitionistic linguistic hybrid geometric (IVILHG) operator, are proposed, and some desirable properties of these operators are established. Furthermore, by using the IVILWG operator and the IVILHG operator, a group decision making approach, in which the criterion values are IVILNs and the criterion weight information is known completely, is developed. Finally, an illustrative example is given to demonstrate the feasibility and effectiveness of the developed method.